1997
DOI: 10.1093/ajcn/65.6.1882
|View full text |Cite
|
Sign up to set email alerts
|

Heart disease risk-factor status and dietary changes in the Cretan population over the past 30 y: the Seven Countries Study

Abstract: A follow-up study was conducted to identify the heart disease risk-factor status and dietary changes of surviving elderly subjects in Crete who took part in the Seven Countries Study in 1960. In 1991, data were obtained from 245 of the 686 original male participants (169 of the original 40-49-y age group and 76 men 50-59 y age group). In 1991, the men were 70-79 and 80-89 y old. There was a significant (11.5%) increase in serum total cholesterol concentrations between 1960 and 1991. Body mass index and systoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
103
1
21

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(129 citation statements)
references
References 10 publications
4
103
1
21
Order By: Relevance
“…Subsequently, the Lion Diet Heart study revealed a smaller incidence in the number of re-infarction and death in 50-70% of subjects who, after a first infarction, followed the MD enriched in a-linolenic acid, in addition to standard diet. Such a result was seen after 27 months, but was also confirmed after 46 months [21][22][23]. Confirmations have subsequently been obtained from many investigations about the MD, highlighting a low frequency in several pathologies (hypercholesterolaemia, hypertension, atherosclerosis, diabetes, and obesity).…”
Section: Towards Evidence-based Medicinesupporting
confidence: 57%
See 1 more Smart Citation
“…Subsequently, the Lion Diet Heart study revealed a smaller incidence in the number of re-infarction and death in 50-70% of subjects who, after a first infarction, followed the MD enriched in a-linolenic acid, in addition to standard diet. Such a result was seen after 27 months, but was also confirmed after 46 months [21][22][23]. Confirmations have subsequently been obtained from many investigations about the MD, highlighting a low frequency in several pathologies (hypercholesterolaemia, hypertension, atherosclerosis, diabetes, and obesity).…”
Section: Towards Evidence-based Medicinesupporting
confidence: 57%
“…In fact, it was found that the MD, in which the lipidic component is somewhat high (>25-30% of total calories, and is represented almost entirely by EVOO, rich in MUFA oleic acid, reduced some risk factors, such as hypercholesterolaemia, atherosclerosis and hypertension, and mortality for cardiovascular diseases. Moreover, a decrease of 56% in total mortality and 61% in cancer risk was seen [14][15][16]21]. In the Seven Countries study (Italy, Greece, Ex-Yugoslavia, Holland, Finland, USA, and Japan, a study on human subjects between 40 and 59 years old), atherosclerotic cardiovascular disease fluctuated between 2 and 10% in southern Europe, where the MD is widespread and the use of EVOO is high (Turkey: 1 kg/year; Italy and Spain: 10-12 kg/year), while it was 10-18% in Northern Europe and USA (USA: 0.45 kg/year).…”
Section: Towards Evidence-based Medicinementioning
confidence: 99%
“…More detailed studies, however, also show that Greek men and women have high fasting triglyceride levels and high postprandial lipaemic changes. Katan and ourselves have therefore expressed surprise that the IHD morbidity and mortality rate are not higher (Aravanis et al, 1988;Kafatos et al, 1997). A lag time might be the confounding factor, this lag probably being greater for disease development than disease remission.…”
Section: Lipid Changesmentioning
confidence: 97%
“…Evidence from subsequent surveys, however, suggests that the prevalence of CVD among Cretans has been increasing rapidly during the past two-three decades (Voukiklaris et al, 1996), and CVD now constitutes the primary cause of morbidity and mortality nationally (Chimonas, 2001). This trend comes at odds to what is observed in most developed countries, and has been attributed mainly to overall lifestyle modifications, such as adverse dietary practices (Kafatos & Mamalakis, 1993;Kafatos et al, 1997), diminished physical activity , and limited health awareness of contemporary Greeks. At the same time, a number of conventional risk factors, and especially obesity (Mamalakis & Kafatos, 1996;Pitsavos et al, 2003) and dyslipidaemia Voukiklaris et al, 1996;Pitsavos et al, 2003), are very common nowadays and, undoubtedly, confer increased CVD risk to Greek subjects.…”
Section: Introductionmentioning
confidence: 96%